The impact of physical activity on mental disorders - Jakubowska, Katarzyna; Jerzak, Aneta; Janocha, Aleksandra; Ziemba, Paweł (Quality in Sport, 2024)
Introduction According to the WHO, health includes mental and social well-being, not just the absence of disease. Mental disorders are common and burdensome, with primary treatments being antidepressants and antipsychotics. However, regular physical exercise improves mental well-being and helps prevent depression, anxiety, and sleep disorders. Given the high prevalence of psychiatric disorders and their association with sedentary behavior and physical illnesses, promoting physical activity is crucial. Exercise reduces the risk of major diseases and enhances cognitive and physical health, including reducing depressive symptoms and increasing neural plasticity. Materials and methods The literature available in the PubMed database was searched using terms such as ‘’physical activity’’ in mental disorders. Results Physical activity (PA) effectively reduces symptoms and enhances cognitive functions in depression, schizophrenia, bipolar disorder, anxiety disorders, and ADHD. Beneficial exercises include walking, jogging, strength training, and yoga. In schizophrenia, PA improves symptoms and cognitive functions, mitigates medication side effects, and enhances well-being. For bipolar disorder, PA reduces mood swings and aids long-term management. Anxiety disorders and ADHD also benefit from PA, with resistance training, yoga, aerobic exercise, and swimming reducing symptoms and improving cognitive functions. Conclusions Regular physical activity significantly benefits psychiatric disorders and should be included as a complementary therapy. Further studies are needed to optimize PA interventions for better mental health outcomes.